Personal Branding Strategy Of @Dewohandiko In Promoting Marine Tourism On Instagram - Aset Malius; Sri Narti; Dilmai Putra (Multidisciplinary Journals, 2026)
Instagram has become an important digital communication platform for building personal identity and promoting local tourism. This study aims to analyze the personal branding strategy of @dewohandiko in promoting marine tourism through Instagram. This research used a descriptive qualitative approach by examining Instagram content, visual narratives, captions, audience interaction, and supporting documentation. The analysis was based on Peter Montoya’s eight principles of personal branding, namely specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. The findings show that @dewohandiko builds a consistent personal image as a maritime tourism communicator through visual content, educational messages, and active engagement with audiences. His specialization is reflected in the focus on marine tourism content, while leadership appears through his role as a maritime ambassador who promotes environmental awareness. His authentic personality, consistent visibility, and positive interaction strengthen public trust. This study concludes that personal branding through Instagram can support tourism promotion by creating a credible, attractive, and socially meaningful image.